1987
DOI: 10.1111/j.1399-6576.1987.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol emulsion for induction and maintenance of anaesthesia. A combined technique of general and regional anaesthesia

Abstract: To provide general anaes hesia with endotracheal intubation during regional blockades, three dose regimens of propofol emulsion were studied: induction 2 mg kg‐1, infusion rate 9 mg kg‐1 h‐ (Group I); induction 2.5 mg kg‐1, infusion rate I? mg kg‐1 h‐1 (Group 2); induction 2.5 mg kg‐1, infusion rate 9 mg kg‐1 (Group 3). Each group comprised 10 healthy (ASA class 1 or 2) unpremedicated patients. The induction times measured from the start of injection until counting ceased (± 50 s) and until eye‐lash reflex dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…They speculated that propofol had some residual effect in the early recovery period after short-duration anesthesia. In addition, propofol has been shown to produce a positive mood or euphoric state postoperatively in adults [15,16]. These effects may also occur in young children.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that propofol had some residual effect in the early recovery period after short-duration anesthesia. In addition, propofol has been shown to produce a positive mood or euphoric state postoperatively in adults [15,16]. These effects may also occur in young children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that propofol anesthesia would increase salivation. [810] For this reason, TIVA is not suggested for ocular surgery. However, the incidence of postoperative nausea and vomiting (PONV) and the need for antiemetics were significantly less in the TIVA patients than in the inhalation anesthesia patients in ophthalmic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had showed that propofol anesthesia would increase salivation. [68] In our hospital, we also found that some patients had nasopharyngeal secretions toward the eye resulting in contamination of surgical field in propofol-based total intravenous anesthesia (TIVA) in ophthalmic surgery. [9] Besides, Bautista and Keech [10] reported 2 cases under propofol anesthesia with excess nasopharyngeal secretions resulting in surgical contamination in strabismus surgery.…”
Section: Introductionmentioning
confidence: 99%